In this question, you are given the *k*th term of a sequence. This means that if you plug in a value of *k*, you will get the term of the sequence numbered* k*. For example,

the first term, `P_1` will have *k* = 1 and `P_1 = 2^(1-1)/(1!) = 1/1 = 1` ,

the second term, `P_2` , will have *k *= 2 and `P_2 = 2^(2-1)/(2!) = 2^1/(1*2) = 1` ,

the third term, `P_3` , will have k = 3 and `P_3 = 2^(3-1)/(3!) = 2^2/(1*2*3) = 4/6=2/3` ,

and so on.

Note that the exclamation sign after k is called "factorial" and it means multiplying all integers starting with 1 and up to k:

`k! = 1*2*3*....(k-1)*k`

So, to find `P_(k+1)` , we need to plug in k+1 instead of k, that is, substitute k+1 for every k in the expression for `P_k` and then simplify:

`P_(k+1) = 2^(k+1 - 1)/((k+1)!) = 2^k/((k+1)!)`

**This corresponds to the answer choice B.**